The Narrative Philosophy of Rational Approach in Islam Abstract (The Case of Qadi Abd Al-Jabbar) - Eraslan, Abdulvasıf (CUMHURIYET UNIV, 2020)
Sunnah is considered the second of the main sources of Islam. The reports, which are considered the carrier of the sunnah, have been conveyed by narrators at different levels. The reasons for the difference between the conveying narration levels were handled mainly as a subject of research and discussion by theologians and Mu'tazila scholars as well. One of these subjects is the factors affecting the conveying of the narration and what is preventing it from being conveyed. Qadi Abd Al-Jabbar (d. 415/1025) is one of the scholars who has a different account on this subject. He developed a philosophical perspective on the Islamic narrative case, acting in line with the rationalist sectarian approach. Accordingly, the frequency of conveying narration, whether the report is religious, its effect on the interlocutor, it's becoming ordinary. Therefore, in this study, the factors which affect conveying of the khabar are emphasized in line with the opinions of Qadi Abd Al-Jabbar. In other words, the factors that ensure that a report is voiced and repeated by the members of the society and the reasons that prevent the transfer of a word are emphasized. Qadi Abd Al-Jabbar dealt with the factors affecting the conveying or repetition of khabar with the social, psychological and belief aspects of human and tried to exemplify. These factors have a two-way effect. Some of factors require the conveying of the khabar, while others are considered to prevent and weaken it. Although these factors are related to the psychological aspect of the person in terms of source, they differ from the process of action. The first of these factors that require the conveying of the khabar was named by Qadi Abd Al-Jabbar as The second one is the factors that prevent the communication of the khabar, and it was named as. The "dai" for doing or not taking an action can be more than one and also different in strength. The action of the person towards the conveying of the khabar is directly proportional to the force of the "dai". Strong actions motivate the person to perform it more, whereas the weakest influence lead less people to perform the action. Therefore, two khabar with the same "dai" should be conveyed at the same rate. Because the main factor is named "dai" that provides their conveying has the same force. Accordingly, it is not correct whether one of the two khabar items that share the same situation and are in the same time period is not posted and the other is. In other words, the transfer of something is devai / and in accordance with the strength of the need within the framework of the custom / law. The conveying of the khabar status depends on the tendency to post it or the issues that prevent it. Among these factors, the issues that enable the conveying of the khabar and motivate people in this regard are also expressed in terms of issues and elements that prevent people from conveying. These are closely related to the psychological situation of the person who conveyed the khabar, the ordinariness of the khabar, the need for the khabar, the distance to the time of the khabar, the religious quality of the khabar and whether there is a fear situation surrounding the conveying. According to this, if there is a "dai / motive" and " devai / motives" related to the khabar, it is conveyed but if there is any "sarif/ inhibitor" about it, it is not conveyed. The "da'i / motive" and "sarif/ inhibitor" of the khabar do not have the same strength. Accordingly, to obtain neccecity in knowledge, the correctnes of khabar depends on the "dai" in the khabar. Therefore, since the "dai" owned by the "khabar from single persons / ahad khaber" are weaker than the "dai" owned by the mutawatir khabar. Therefore, it cannot be expected to be transmitted at the same level.
Keywords: Hadith; Mu'tazila; Qadi Abd Al-Jabbar; Narration Philosophy; Conveying of Khabar